Faktor-Faktor yang Berhubungan dengan Kejadian Bayi Berat Lahir Rendah (BBLR) - Nurul Azmi Eka Rinie; Fiky Jayanti; Puji Lestari; Ayi Hernani Putri; Rusni Masnina (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Low Birth Weight (LBW) refers to infants born with a birth weight of less than 2,500 grams and remains an important issue in neonatal health due to its association with increased neonatal morbidity and mortality. To analyze the determinants of LBW based on primary studies published from 2021 to 2026. A literature review was conducted using the PRISMA approach. Article searches were performed through PubMed, Google Scholar, Scopus, ScienceDirect, and ProQuest using the keywords low birth weight, determinant factors, risk factors, BBLR, and faktor risiko with Boolean operators AND/OR. The inclusion criteria were primary studies, full-text availability, publication in Indonesian or English, and publication years from 2021 to 2026. A total of 20 articles were included, consisting of 15 international articles and 5 national sources. The review showed that LBW is influenced by interrelated maternal, nutritional, obstetric, and sociodemographic factors during pregnancy. The most dominant factors included multiple pregnancy with an adjusted OR of 21.74, maternal food insecurity with an AOR of 6.85, maternal hemoglobin level <11 g/dL with an AOR of 5.21, lack of iron-folic acid supplementation with an AOR of 4.17, maternal age ≤20 years with an AOR of 3.42, pregnancy interval <1 year with an adjusted OR of 2.92, missed antenatal care visits with an AOR of 2.74, smoking during pregnancy with an OR of 2.18, and maternal hypertension with an AOR of 1.94. LBW is influenced by multiple interrelated factors; therefore, efforts to reduce its incidence should focus on evidence-based interventions, particularly through optimizing antenatal care services, improving maternal nutritional status, and early detection of pregnancy.